2019
DOI: 10.3390/en12224280
|View full text |Cite
|
Sign up to set email alerts
|

Energy Accounting for a Renewable Energy Future

Abstract: For millennia, humans relied almost entirely on renewable energy (RE), largely biomass, for their energy needs. Over the past century, fossil fuels (FFs) have not only largely replaced RE, but have enabled a many-fold rise in total energy use. This FF dominance changed the way we think about and accounted for energy use. If (as at present) the world essentially continues to ignore climate change, eventual resource depletion will force conversion to RE and, perhaps, nuclear energy will once again have to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 79 publications
0
25
0
1
Order By: Relevance
“…The availability of a green energy supply, however, is generally a crucial factor. Based on the expected worldwide transition towards increasing renewable energy production in the coming decades [65], carbon footprints of energy provision might need a new way of quantification [66,67]. This is in no way a criticism on certain universities for having a higher CF than others.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of a green energy supply, however, is generally a crucial factor. Based on the expected worldwide transition towards increasing renewable energy production in the coming decades [65], carbon footprints of energy provision might need a new way of quantification [66,67]. This is in no way a criticism on certain universities for having a higher CF than others.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that a figure of 350 ppm for CO2 in the atmosphere is considered as the safe 'planetary boundary' [1]. However, it was reported that the atmospheric concentration of CO2 has already passed 407 ppm in 2018 [12]. On the other hand, it is generally acknowledged that the frequency of occurrence of extreme meteorological events have been increasing over the past decades [12].…”
Section: Share Of Global Primary Energy Supply By Source a Global Renewable Energy Statisticsmentioning
confidence: 99%
“…In the same fashion, the measurement unit of all kinds of energy production i.e. biogas energy BE, wind energy WE and solar energy SE have been taken as billion kilowatt hours (Moriarty and Honnery, 2019). Not only these, but the same unit has also been taken for energy consumption EC, the only control variable of the study.…”
Section: Model Specificationmentioning
confidence: 99%